Metronome vs. Popular Song: A Comparison of Long-Term Retention of Chest Compression Skills after Layperson Training for Cardiopulmonary Resuscitation. Issue 3 (May 2016) - Hong, CK; Hwang, SY; Lee, KY; Kim, YS; Ha, YR; Park, SO
Introduction: Long-term retention of cardiopulmonary resuscitation (CPR) skill is challenging for layperson trainees. This study compared the long-term retention of chest compression skills after either metronome-guided (MG) or popular song-guided (PG) CPR training. Methods: This was a prospective randomised simulation trial. Untrained laypersons were randomly allocated to MG (n=61) or PG (n=68) groups at CPR training sessions. After CPR training, each participant performed 5-cycle CPR using a manikin with a Skill-Reporter™ immediately and six months afterwards. Results: Immediately after training, the mean compression rate (MCR) was slightly higher in the PG than the MG group (107.4 vs. 102.2/min; p<0.0001), but there was no significant difference in the proportions of participants with an appropriate chest compression rate (100-120/min) (PSACCR) between the MG and PG (53/61 (86.9%) vs. 65/68 (95.6%); p=0.114). Six months later, MCR was faster in the MG than the PG (124.8 vs. 110.0/min; p<0.0001), and PSACCR in the PG was higher than that in the MG (62/68 (91.2%) vs. 25/61 (41.0%); p<0.0001). In both tests, there were no significant differences in other chest compression parameters of between the two groups, except for a minimal difference in incomplete chest release. Conclusion: CPR training using a popular song is more effective than metronome-guided training in helping laypersons to maintain recommended compression rates after 6 months. (Hong Kong j.emerg.med. 2016;23:145-152)